An Analysis of Writing Anxiety of the Second Semester Student at English Language Study Program of FKIP UIR - Dewi Popita Sari; Fauzul Etfita (DISCOVERY JOURNAL, 2022)
The objective of this research is to find out writing anxiety of the second semester students’ at English Language Education study program of FKIP UIR. The design of this research is mixed method that consist of descriptive research and qualitative research approach. The participants of this study were 50 students of class B. The researcher chose the sample randomly. The researcher uses two kinds of questionnaires as the research instruments. The first questionnaire is adapted from Masriani (2018), while the second questionnaire was adapted from Rezaei & Jafari (2014). Analysis of data from this study was applied by using a likert scale. The result from questionnaire showed that students know about types and causes of their writing anxiety. Besides that, they also get some benefits from knowing the types and causes writing anxiety, such it makes them to learn more and prepare themselves before writing. So, they become confidence to write, without having the anxious feeling.